2013
DOI: 10.5546/aap.2013.eng.516
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in students from different altitudinal zones of Jujuy according to three international references (IOTF, CDC and WHO)

Abstract: Introduction. Prevalences of overweight and obesity in students from different altitudinal zones of Jujuy are compared using the International Obesity Task Force (IOTF), the Centers for Disease Control (CDC) and the World Health Organization (WHO) references, and the agreement among them. Material and Methods. Weight and height data from 15 541 students were grouped in highlands (HL) (≥2500 MASL) and lowlands (LL) (<2500 MASL) and in two age groups (5-6.99 years old and 11-12.99 years old). Overweight and obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The use of the IOTF classification system may have led to a slight underestimation of the prevalence of overweight and obesity compared to other reference frameworks used on an international level, such as those recommended by the Center for Disease Control (CDC) in the United States (Hajian‐Tilaki & Heidari, ; Pedrosa et al, ). However, most studies have found that there is good agreement between the IOTF and the CDC criteria for the identification of both overweight and obesity (Hajian‐Tilaki & Heidari, ; Li et al, ; Meyer, Carrillo, Roman, Bejarano, & Dipierri, ; Pedrosa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of the IOTF classification system may have led to a slight underestimation of the prevalence of overweight and obesity compared to other reference frameworks used on an international level, such as those recommended by the Center for Disease Control (CDC) in the United States (Hajian‐Tilaki & Heidari, ; Pedrosa et al, ). However, most studies have found that there is good agreement between the IOTF and the CDC criteria for the identification of both overweight and obesity (Hajian‐Tilaki & Heidari, ; Li et al, ; Meyer, Carrillo, Roman, Bejarano, & Dipierri, ; Pedrosa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Meyer et al 40 carried out in Argentina, when analysing the prevalence of obesity calculated with the different references, observed that the WHO reference gave the highest rates (29.3% compared to the CDC of 17.6% and the IOTF of 10.1%). For obesity, the differences between references were significant in all comparisons, except between the IOTF and the CDC in both sexes and age groups.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of children, young people and adolescents affected by overweight varies considerably depending on the BMI cut-off points across classifications and may also vary by age group and ethnicity. 40 , 59 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, owing to the absence of a widely-shared consensus, it is highly recommended that prevalence studies consider several reference values [30], specifically international standards such as the ones from the IOTF and at a national level the OF criteria. Thus, it is well known that results and their comparison in terms of overweight and obesity prevalence is highly dependent on the methodology used [31,32]. Therefore, in our study both criteria were used to determine overweight/obesity prevalence at the baseline and at the end of the follow-up period.…”
Section: Discussionmentioning
confidence: 99%